Oil consumption in 4WD farm tractors used in forestry operations - Airoldi, Gianfranco (Array, 2020)
Farm tractors are still widely used in many forestry operations. Predicting fuel and lubricant costs is difficult because their consumption depends on a number of factors such as hours worked and operations performed. Fuel and lubricant consumption is important since it can have an impact at both the economic and environmental level. Many fuel models have been studied in the last decades, but few studies have focused on oil consumption. The ASABE (American Society of Agricultural and Biological Engineers) Standard suggested a model for predicting engine oil consumption of farm tractors of the 1980s, which are potentially different from modern tractor engines. In addition, the recent widespread application of semi- and full-power-shift and continuous variable transmissions and the high number of hydraulic applications increased the amount of lubrication oil for transmission and hydraulic systems.For these reasons, we analysed 133 4WD recent model farm tractors used in forest operations with the aim to study:Þ engine, transmission and hydraulic system oil capacitiesÞ engine oil change intervals as recommended by the manufacturers.A new equation for engine oil consumption, as a function of the rated engine power, was first used and statistically analysed. It was similar to the equation developed by other authors (with a mean difference of 28%, decreasing to 11% at the highest engine power), but well below the ASABE model (with an average engine oil consumption three times higher). Another equation of total oil consumption related to the rated engine power was then studied and compared with a recent study. The results showed an average difference of 18%, decreasing to 8% at the highest engine power.